The Meaning, Function, and Solution of Hate in Youth: A Sex-Based Analysis - Valdez Medina, José Luis (Consorcio de Universidades Mexicanas A.C., 2012)
The objective of this study was to determine what is the meaning, function and how to solve the most significant situations of hate that have experienced young men and women throughout their lifes. The type of study is descriptive; we worked with a probabilistic sample of intentional type, composed of 400 college students aged between 17 and 23 years, divided equally by sex. We used a questionnaire consisting of 6 open-ended questions to assess the design and solution forms of hatred in the participant: What is hate?, In what situations arises hatred?, Why do people hate?, ¿What get people to hate, What prevents people to hate, and how do the people solves a situation of hate? Men and women report feeling hatred as a negative character, which creates resentment and can be expressed or repressed. Men see hatred as a psychological and physiological reactions that lead to the outside, while women appreciate it as a feeling that can point to themselves, as a matter of self-destruction. Men and women agree that the possible solutions of hatred may be those that are socially accepted, such as communication, getting help, the full expression of hatred, love, the pursuit of defenses and the neglect of the situation, while other possible alternatives that may not be accepted as the best in the social context, would be assault and attempted assassination of the hated person.